Answer:
see explanation
Explanation:
Given the recursive formula
= 3
+ 2 and a₄ = 20
Then working in reverse
3a₃ + 2 = 20 ( subtract 2 from both sides )
3a₃ = 18 ( divide both sides by 3 )
a₃ = 6
3a₂ + 2 = 6 ( subtract 2 from both sides )
3a₂ = 4 ( divide both sides by 3 )
a₂ =
![(4)/(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/njuue06kwccysinu3fvpfi1udnx59yqvei.png)
3a₁ + 2 =
( subtract 2 from both sides )
3a₁ = -
( divide both sides by 3 )
a₁ = -
![(2)/(9)](https://img.qammunity.org/2020/formulas/mathematics/high-school/lhbvrlxgn7zlwju7c5k5ocx2nstp3fh6kq.png)
Hence
a₁ = -
![(2)/(9)](https://img.qammunity.org/2020/formulas/mathematics/high-school/lhbvrlxgn7zlwju7c5k5ocx2nstp3fh6kq.png)
a₂ =
![(4)/(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/njuue06kwccysinu3fvpfi1udnx59yqvei.png)
a₃ = 6